Faktor-Faktor yang Mempengaruhi Penerapan Teknologi Budidaya Stroberi serta Dampaknya terhadap Produksi dan Pendapatan Petani di Desa Sukaresmi - Ning Srimenganti (Ma'soem University, 2023)
The purpose of this study was to determine the factors affecting the application of strawberry cultivation technology and How the impact of the application of strawberry cultivation technology On the production and income of farmers in Sukaresmi village, Rancabali district, Bandung regency. The research method used is a survey method. The unit of analysis is the strawberry farmer. The technique of determining the respondents is done by using probability sampling with Simple Random Sampling technique and using the Slovin formula. The number of respondents studied was 62 people. The results showed that the internal factors (age, length of farming, land area, capital) and external factors (selling price, marketing, labor, agricultural extension) simultaneously affect the application of strawberry cultivation technology and there is a significant effect. between the application of Strawberry Cultivation Technology with production and income in Sukaresmi Village, Rancabali District, Bandung Regency.